Interaction of miRNAs with mRNAs of MYB transcription factors gene family in Arabidopsis (Experimental biology, 2015)
The binding sites for 40 miRNAs in mRNAs of MYB gene family in Arabidopsis were identified. miR828 and miR858 target 14 and 13 genes respectively. 16 and 20 MYB family genes were targets for miR5021 and miR5658 respectively. Multiple binding sites with starts located sequentially in 1-3 nucleotides in mRNAs of miR5021 and miR5658 targetswere revealed. miR159 and miR319 families had common binding sites in six MYB mRNAs. 26 miRNAs had one binding site in the mRNAs of 23 MYB genes. All miRNA binding sites were located in the protein coding sequenceof target mRNAs. The nucleotide sequence of each miRNA binding site were homologous and encoded homologousoligopeptides.
Keywords: miRNA; mRNA; MYB; binding site; arabidopsis.